(untitled) (GnosisWisdom, 2022)
Objective To estimate the effectiveness of the preventive strategy "Adult Care" in the clinical profile and metabolic biomarkers of adults with arterial hypertension and diabetes mellitus in an Andean region of Peru. Methodology. The study carried out used the general inductive - deductive method. The sample size was chosen from the whole number of the list of patients treated at the Huancavelica hospital, in the diabetes and hypertensive service, the list of adults whose results were entered into an Excel table, so that it would automatically come out randomly. selected adults. For data collection, the dependent variable was used: Clinical profile and metabolic biomarkers of HBP and DM. Regarding the technique for measuring the variable, the technique of documentary analysis, survey and questionnaires was used. The instrument is the format for recording data on adults with risk factors and the case of NCD. Adults of age were recruited when there was a demand for the diabetes and hypertensive program services at the Huancavelica hospital, in which 569 adults were estimated as a goal. Results. According to the study carried out after the educational intervention strategy, the following results were obtained: presenting 63.3% of normal BMI, 60.0% systolic pressure, 56.7% diastolic pressure, 53.3% of metabolic biomarkers-cholesterol , 46.7% triglycerides, 56.7% HDL, 70% LDL normal values in hypertensive patients, 80.0% normal glycemia, 50.0% BMI, the results were obtained in type 2 diabetic patients, as well as knowing the characteristics of the disease and the treatment and the physical conditions to avoid complications of the disease. The educational interventions seem to have contributed positively to the participants’ knowledge about type 2 diabetes mellitus and arterial hypertension, adherence to treatment showing effectiveness and improvement in adults. Conclusions. Statistical evidence showed us that preventive strategies contribute to improving "adult care" in the clinical profile and metabolic biomarkers of adults with arterial hypertension and diabetes mellitus.